Tick Salivary Kunitz-Type Inhibitors: Targeting Host Hemostasis and Immunity to Mediate Successful Blood Feeding - Jmel, Mohamed Amine; Voet, Hanne; Araújo, Ricardo N; Tirloni, Lucas; Sá-Nunes, Anderson; Kotsyfakis, Michail (International journal of molecular sciences, 2023)
Kunitz domain-containing proteins are ubiquitous serine protease inhibitors with promising therapeutic potential. They target key proteases involved in major cellular processes such as inflammation or hemostasis through competitive inhibition in a substrate-like manner. Protease inhibitors from the Kunitz superfamily have a low molecular weight (18-24 kDa) and are characterized by the presence of one or more Kunitz motifs consisting of α-helices and antiparallel β-sheets stabilized by three disulfide bonds. Kunitz-type inhibitors are an important fraction of the protease inhibitors found in tick saliva. Their roles in inhibiting and/or suppressing host homeostatic responses continue to be shown to be additive or synergistic with other protease inhibitors such as cystatins or serpins, ultimately mediating successful blood feeding for the tick. In this review, we discuss the biochemical features of tick salivary Kunitz-type protease inhibitors. We focus on their various effects on host hemostasis and immunity at the molecular and cellular level and their potential therapeutic applications. In doing so, we highlight that their pharmacological properties can be exploited for the development of novel therapies and vaccines.
Keywords: Serine Proteinase Inhibitors; Serpins; Cystatins; inhibitory serinových proteinas; Kunitz-type; protease inhibitors; ticks; sliny; Ticks; klíšťata; Animals; Saliva; hemostasis; serpiny; parasite-host interactions; zvířata; immunomodulation; cystatiny